HUBUNGAN SHIFT KERJA DENGAN TERJADINYA KELELAHAN PADA SECURITY SUN PLAZA MEDAN TAHUN 2015 - erizka yulinda; Halinda Sari Lubis; Isyatun Mardiah Syahri (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT The high rate of crime causes demand for security services increased especially at public places, such as shopping centers. Demand for 24-hour safety requires the security workers have to make a work shift that can cause them feel exhausted. Therefore, the study was done, about “The correlation of Work Shift to fatigue occurrence of SUN Plaza Medan Security Workers in 2015”. The study method is analytical survey with cross sectional design. The sample which is taken are 56 of 113 populations with purposive sampling, types of shift are 2 days for the morning shift, 2 days for the night shift, and 2 days off. The fatigue is measured in every shift by using fatigue questionnaire subjectively with the scale of Industrial Fatigue Research Committee (IFRC) and categorized into low, medium, high and very high level. The study result which is found is the fatigue level for the morning shift, the most is at medium level which is 36 people (64.5%), low level which are 19 people (33.9%) and the high level is only 1 person (1.8%). On the night shift, the most is at medium leve which are 45 people (80.4%) while the rest is at a higher level which are 11 people (19.6%). In chi square test results got that there is a correlation between the work shift and the fatigue occurence cause (p=0.002). It is advisable to security workers who work for the night shift, in order to realize that the responsibility which is given to them is not the workload of job but as an obligation which has to be done. In addition, utilize day time for sleeping and take a rest well. The company also suggested conduct socialization about the workload especially psychological burden and the way to overcome it as well as arranging the time of working and resting to security workers in order not to cause the fatigue on night shift.